1982
DOI: 10.1111/j.1600-0765.1982.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supervised chlorhexidine mouthrinses in children

Abstract: The study tested the effects of supervised chlorhexidine digluconate (CH) mouthrinses on plaque and gingivitis in school children. 158 children (aged 10–12 years) participated in the study. They were divided into four groups matched according to age, sex. DMFS, and GI. Following a sealing and prophylaxis procedure. Group A was assigned to daily mouthrinses 6 times per week using a .2 % solution of CH. Group B used the same solution only twice per week, and Group C was assigned to daily rinsing using a .1 % sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
0
11

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(115 citation statements)
references
References 20 publications
9
95
0
11
Order By: Relevance
“…Side effects have been reported after the utilization of chlorhexidine, specially regarding its bitter taste. The presence of dental pigmentation in groups II and III confirms this side effect as the most frequently detected in the majority of the studies on chlorhexidine, in adults and children 11,21 . Disregarding the alteration observed in these two groups, no irritation or desquamation of the oral mucosa were observed, neither were burning or dryness symptoms reported.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Side effects have been reported after the utilization of chlorhexidine, specially regarding its bitter taste. The presence of dental pigmentation in groups II and III confirms this side effect as the most frequently detected in the majority of the studies on chlorhexidine, in adults and children 11,21 . Disregarding the alteration observed in these two groups, no irritation or desquamation of the oral mucosa were observed, neither were burning or dryness symptoms reported.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, it has already been demonstrated that mouthrinses with chlorhexidine, in different concentrations, frequencies of use, and quantities, prevent the formation of dental plaque 11,15 . Employing the same rou- tine as that carried out in group II during 6 weeks, Zanela 21 (1995) observed a reduction of 52.63% in the mean score of plaque, which is in agreement with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of 0.12 or 0.2% CHX mouthwash significantly reduce plaque and gingivitis. [21][22][23] The antibacterial properties of these products have been demonstrated in vitro as well as in vivo. 24,25 The studies comparing CHX with other active agents such essential oils, sanguinarine, and delmopinol provide enough evidence on the superiority of CHX.…”
Section: Chlorhexidine (Chx)mentioning
confidence: 99%
“…6 A lower concentration of CHX (0.12%) has been tested in animals and human populations and has also demonstrated clinical benefits. 7,13,14 Although CHX is an effective antimicrobial agent in both concentrations, comparison of the two existing formulations is still necessary. The aim of the present study was to assess the efficacy of two concentrations of chlorhexidine solutions (0.12% and 0.20%) on plaque development and gingival bleeding control during 14 days.…”
mentioning
confidence: 99%